2016
DOI: 10.1515/rjim-2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

ST Segment Elevation Myocardial Infarction Due to Severe Ostial Left Main Stem Stenosis in a Patient with Syphilitic Aortitis

Abstract: Cardiovascular manifestations of tertiary syphilis infections are uncommon, but represent an important cause of mortality and morbidity. Syphilitic aortitis is characterized by aortic regurgitation, dilatation of ascending aorta and ostial coronary artery lesions.We report a case of 36 years old man admitted to our hospital for acute anterior ST segment elevation myocardial infarction complicated with cardiogenic shock (hypotension 75/50 mmHg). Transthoracic echocardiography revealed a dilated left ventricle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…PCI is recommended within first 12 h from onset of symptoms [7], CABG is preferred if there are stable angina or delayed admission from presentation [2,8]. There are no comparative studies of PCI versus CABG in treating syphilitic COS [9], and potential anastomotic stenosis or restenosis in-stent restenosis caused by continuous infection of the ascending aorta may exist [2]. In the present case, we anastomose SVG to the bovine pericardium to avoid this situation, long-term follow is mandatory as a result of potential anastomotic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…PCI is recommended within first 12 h from onset of symptoms [7], CABG is preferred if there are stable angina or delayed admission from presentation [2,8]. There are no comparative studies of PCI versus CABG in treating syphilitic COS [9], and potential anastomotic stenosis or restenosis in-stent restenosis caused by continuous infection of the ascending aorta may exist [2]. In the present case, we anastomose SVG to the bovine pericardium to avoid this situation, long-term follow is mandatory as a result of potential anastomotic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The treponemes initially infect the adventitial vasa vasorum of the aorta, inducing perivascular lymphoplasmacytic inflammation and leading to endarteritis obliterans, median destruction, and intimal thickening and wrinkling [ 5 ]. Syphilitic aortitis can thus also cause aortic regurgitation and coronary artery ostial narrowing, related to aortic wall thickening [ 6 ]. Our patient was later revealed to be positive for syphilis antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Active vasculitis was negative, but his coronary ostial stenosis was probably the result of a syphilis infection incurred more than 10 years ago. Although no aortic root dilatation was seen, it is reasonable to speculate that the weakening of the aortic wall caused the aortic regurgitation [ 6 ]. Cardiovascular syphilis can cause aortic aneurysm, aortic regurgitation, and coronary artery ostial stenosis [ 7 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Late-stage syphilis frequently involves the cardiovascular system, with an incidence as high as 10%, occurring 10 to 30 years or more after the initial infection. Cardiovascular syphilis can manifest as isolated aortitis, aortic valve insufficiency, coronary artery stenosis or obstruction, aortic aneurysm, and mucous myocarditis [7][8][9].…”
Section: Epidemiologymentioning
confidence: 99%
“…In the case of patients with acute myocardial infarction (AMI) who have no personal history, family history, or risk factors for coronary atherosclerosis, especially those who exhibit coronary artery membrane lesions on coronary angiography or those without distal coronary artery lesions, vigilance for arteritis-related conditions is essential. Currently, the exact incidence of syphilitic aortitis is unclear, but a clinical pathological study of 100 cases showed that only 17% of patients were clinically diagnosed with syphilitic aortitis [9].…”
Section: Pathogenesismentioning
confidence: 99%